Pengaruh Lingkungan Kerja, Kecerdasan Emosional, dan Kompensasi Terhadap Kepuasan Kerja Karyawan dengan Motivasi Sebagai Pemoderasi - Budi Budi; Toni Yoyo (eCo-Buss, 2025)
This research aims to explore the influence of the work environment, emotional intelligence and compensation on employee job satisfaction with motivation as a moderator as well. This research uses the Structural Equation Modelling (SEM) method to analyse the relationship between research variables with the help of Smart PLS software. The saturated sampling method was used for research where the entire population of Buddhi College School employees was sampled as 157 respondents. The research results support the proposed hypothesis that the work environment, emotional intelligence, compensation and motivation have a positive and significant effect on employee job satisfaction.  Meanwhile, the research results show that the relationship between motivation and the influence of the work environment on job satisfaction has a positive and significant effect. Meanwhile, the relationship between motivation and the influence of emotional intelligence and compensation on job satisfaction has a negative and significant effect. Implications for organizations, if organizations want to increase job satisfaction, then organizations need to improve the work environment, emotional intelligence, compensation and motivation.